Chalcone derivatives as non-canonical ligands of TRPV1. (July 2019) - Benso, Bruna; Bustos, Daniel; Zarraga, Miguel O.; Gonzalez, Wendy; Caballero, Julio; Brauchi, Sebastian
Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a polymodal cation channel activated by heat, voltage, and ligands. Also known as the capsaicin receptor, TRPV1 is expressed in numerous tissues by different cell types, including peripheral sensory fibers where acts as a thermal and chemical detector in nociceptive pathways. TRPV1 channels are able to bind a wide range of ligands, including a number of vanilloid derivatives all modulating channel's activity. When expressed by sensory neurons, activation of TRPV1 channels by heat (>40 °C), capsaicin (sub-micromolar), or acid environment (pH < 6), causes depolarization leading to burning pain sensation in mammals. Naturally occurring chalcones (1, 3-diaryl-2-propen-1-ones) have been reported as effective inhibitors of TRPV1. Their relatively simple chemical structure and the possibility for handy chemical modification make them attractive ligands for the treatment of peripheral pain. By taking advantage of the structural information available, here we discuss pharmacological properties of chalcones and their putative mechanism of binding to TRPV1 channels.